1984
DOI: 10.7326/0003-4819-100-3-382
|View full text |Cite
|
Sign up to set email alerts
|

Additional Chenodiol Therapy After Partial Dissolution of Gallstones with Two Years of Treatment

Abstract: During the National Cooperative Gallstone Study, therapy with chenodiol, 750 or 375 mg/d, for 2 years resulted in confirmed, complete gallstone dissolution in 14% and 5% of patients, respectively, and partial dissolution (greater than 50%) in 27% and 18%. The present study was done to determine the frequency with which complete dissolution occurs in patients having partial dissolution of gallstones who receive additional therapy. Eighty-six of one hundred thirty-eight eligible patients continued to receive 750… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…32 We have also shown that bedtime administration of CDCA is more effective than mealtime administration in improving the gall stone dissolution rate. 33 Previous studies have expressed their results in terms of the percentage of patients who achieve partial or complete gall stone dissolution, or both, within a defined time.22-24 26 28 12 34 The disadvantage ofthese studies is that only those patients who achieved complete dissolution are used for statistical analysis, and therefore there is a requirement for large numbers of patients to be enrolled, or for long periods of treatment follow up. This has prevented the demonstration of clearcut differences between the two bile acids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…32 We have also shown that bedtime administration of CDCA is more effective than mealtime administration in improving the gall stone dissolution rate. 33 Previous studies have expressed their results in terms of the percentage of patients who achieve partial or complete gall stone dissolution, or both, within a defined time.22-24 26 28 12 34 The disadvantage ofthese studies is that only those patients who achieved complete dissolution are used for statistical analysis, and therefore there is a requirement for large numbers of patients to be enrolled, or for long periods of treatment follow up. This has prevented the demonstration of clearcut differences between the two bile acids.…”
mentioning
confidence: 99%
“…12 3/9 47(8) 114(4) (2) UDCA (MT) 12 2/10 55 (6) 107 (5) 11-8 (3) UDCA (BT) 12 4/8 55 (9) 102 (6) 12-3 (3) Combination (BT) 10 2/8 50 (6) 118 (5) 13-2 (2) MT= mealtime; BT= bedtime; IBW= ideal body weight * Results expressed as mean (SEM) 0 0 28 0 0 30 25 38 18 20 30 19 23 52 28 10 10 30 27 27 18 48 80 18 8 8 20 25 40 26 43 65 13 45 50 12 50 100 13 100 100 14 68 90 12 65 78 11 100 100 13 75 93 10 60 80 11 27 52 11 0 0 10 73 73 9 90 95 7 47 80 7 100 100 7 85 85 6 80 92 5 0 0 5 40 56 6 26 76 7 70 90 5 50 70 5 90 100 4 80 100 4 100 100 4 50 100 4 100 100 4 100 100 4 100 100 4 36 56 4 60 78 3 85 85 4 DIA=initial gallstone diameter; DR6 and DR12=dissolution rate at 6 and 12 months respectively; *= DR in this matched quartet of patients is calculated from % reduction in pretreatment gall stone numbers.…”
mentioning
confidence: 99%